Pelaksanaan Program CHSE di Homestay Desa Ngargoretno Kabupaten Magelang Jawa Tengah - Herry Kusherdyana; Syaeful Muslim; Hery Soesanto; R. Sondjana Ali Suganda (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2022)
During the pandemic covid-19, tourists tend to prefer outdoor tourism and natural tourism (adventure) including tourism in tourist villages. This condition opens the opportunity for homestay owners in the tourist village to prepare homestays that can guarantee a sense of security for tourists by implementing the CHSE program in their homestays. Therefore, this research aims to uncover the extent of understanding and application of the CHSE program by homestay owners/managers in Ngargoretno Tourism Village, Magelang, Central Java. This study used a qualitative descriptive method by conducting interviews with nine homestay owners and three ngargoretno village officials determined by snowball sampling and Purposive sampling techniques. The results showed that the homestay owners/managers have not fully understood and implemented the CHSE program. Likewise, the public has not fully realized the importance of implementing the CHSE program. Therefore, more intensive socialization and training are needed to the community, especially the owners/managers of homestays about the need for the implementation of CHSE.